Online intervention to prevent postnatal depression and anxiety in Chilean new mothers: Protocol for a feasibility trial. (27th October 2022) - Pérez, J. Carola; Aldoney, Daniela; García, María I; Olhaberry, Marcia; Fernández, Olga; Alamo, Nicolle; Franco, Pamela; Pérez, Francisca; Fisher, Jane; Rowe, Heather; Coo, Soledad
Symptoms of postpartum depression and anxiety in new mothers are prevalent and negatively impact maternal emotional wellbeing and infant development. Barriers to accessing treatment prevent women from receiving mental health care, a situation that has worsened due to the COVID-19 pandemic. mHealth interventions hold the potential to support women during the transition to parenthood despite these barriers and to promote the use of preventive interventions. This study uses a mixed methods design to assess the feasibility and preliminary effectiveness of a psychoeducational, guided mHealth intervention to prevent postpartum mental health difficulties in women who receive care in primary health centers in Chile. The study will contribute to evidence-based research on the effectiveness of mHealth interventions for new mothers from an understudied cultural background. The findings will also enable the development of a larger randomized controlled trial to assess the effectiveness of the intervention, which, if effective, could significantly contribute to the emotional wellbeing of women and their families.